Analisa Pengaruh Parameter Proses FDM Terhadap Kekuatan Tarik Produk 3 Dimensi - Durrani Irdin, Afiq; Pristiansyah, Pristiansyah; Sirwansyah Suzen, Zaldy (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
3D Printing, commonly referred to as Additive Manufacturing, has facilitated rapid advancements and brought significant changes to the manufacturing industry, particularly in revolutionizing production processes. This technology is extensively employed for rapid prototyping, allowing the creation of designs that are both visually perceptible and physically tangible, with actual volume. This research aims to examine the tensile strength of PLA+ filament under various parameter settings and assess their impact using the Taguchi method. The experiments were performed using an FDM Creality Ender 3 Pro 3D printer, which features a printing area of 220mm x 220mm x 250mm and a 0.4 mm nozzle diameter. The parameters investigated include Nozzle Temperature (220°C, 230°C, 240°C), Bed Temperature (65°C, 70°C, 75°C), and Layer Thickness (0.10mm, 0.15mm, 0.20mm). The findings revealed that the optimal tensile strength was achieved in the first trial, with a Nozzle Temperature of 220°C, Bed Temperature of 65°C, and Layer Thickness of 0.10mm, yielding an average tensile strength of 22 MPa across three replications.